Drag reduction with different liquids on slippery liquid-infused porous surface - Tuo, Yanjing; Zhang, Haifeng; Liu, Xiaowei; Song, Keguan (Surface engineering, 2021)
Solid/liquid interface drag reduction is a hot topic and it is of great significance to reduce energy consumption in industrial field. Herein, we prepare a slippery liquid-infused porous surface (SLIPS) with excellent self-healing and super-slippery properties. Through adjusting the density of Zn-Al LDH films on aluminium foil, the ability of rough surface to capture lubricant oil is studied. The SLIPS can repel various liquids such as water, white mineral oil and ethanol. By testing the friction of solid/liquid interface, the drag reduction ratio of SLIPS is 20-30% to water, 10-20% to white mineral oil and 8-12% to ethanol at low velocity. We believe the SLIPS has great potential application in solid/liquid interface drag reduction.